2017
DOI: 10.1038/s41598-017-12220-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of extreme El Niño events on modern sediment transport along the western Peruvian Andes (1968–2012)

Abstract: Climate change is considered as one of the main factors controlling sediment fluxes in mountain belts. However, the effect of El Niño, which represents the primary cause of inter-annual climate variability in the South Pacific, on river erosion and sediment transport in the Western Andes remains unclear. Using an unpublished dataset of Suspended Sediment Yield (SSY) in Peru (1968–2012), we show that the annual SSY increases by 3–60 times during Extreme El Niño Events (EENE) compared to normal years. During EEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 64 publications
1
32
0
1
Order By: Relevance
“…Clearly, the general long-term accretion trends along the coastline of the Callao Bay were mainly due to the sediment discharge during an EN event, and thus Callao Bay was benefiting from the sediment input of big EN events to sustain its coastline. These results are in accordance with other studies that found that SSY in the Peruvian Andes increases significantly during extreme EN events [24], and in the case of the Rimac River, satellite image analysis of the shoreline suggest that this increased SSY is eventually deposited along the Callao Bay.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Clearly, the general long-term accretion trends along the coastline of the Callao Bay were mainly due to the sediment discharge during an EN event, and thus Callao Bay was benefiting from the sediment input of big EN events to sustain its coastline. These results are in accordance with other studies that found that SSY in the Peruvian Andes increases significantly during extreme EN events [24], and in the case of the Rimac River, satellite image analysis of the shoreline suggest that this increased SSY is eventually deposited along the Callao Bay.…”
Section: Resultssupporting
confidence: 93%
“…For example, during the EN in 2017, discharge reached a maximum of 130 m 3 /s, which is two times the average historical value (Figure 3b). It is also shown that during extreme EN events, suspended sediment yield (SSY) of rivers in the Peruvian Andes increase to 30-60 times their average level of normal years [24]. During these events, 82%-97% of SSY occurs between January and April, which coincides with the summer season in the southern hemisphere [24].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Along the western flank of the Peruvian segment of the Central Andes, the cumulative seismic moment is greatest along the subduction interface and is thus below the coastline. This region does not coincide with the catchments yielding the highest decennial suspended sediments, which instead are located further inland, close to the main water divide (Morera et al, ). This observation, together with the restricted volume of coseismic landslides observed in a recent Andean megathrust earthquake (Lacroix et al, ), suggests a low catchment‐wide erosional response to this type of seismic event.…”
Section: Introductionmentioning
confidence: 95%
“…These events have claimed more than 7,600 lives and affected more than 244,000 properties, of which approximately 60,000 were destroyed completely. HGE are common in the flanks of the mountain ranges and valleys and they are related to steep slopes, lithology, heavy rainfall, earthquakes, and an inadequate land use (Zavala and Núñez, ; Vargas et al, ; Villacorta et al, ; Margirier et al, ; Morera et al, ). Their origin is connected with the location of Peru in an active convergent boundary which determines the local geology and tectonic settings (Zavala and Núñez, ).…”
Section: Introductionmentioning
confidence: 99%